On the weal and woe of internet traffic management in Europe: A critical appraisal from a network economic perspective - Volker Stocker (International Telecommunications Society (ITS), 2013)
The Body of European Regulators for Electronic Communications (BEREC) has recently proposed a framework to assess the reasonableness of traffic management (TM) practices. This paper discusses BEREC's proposal from a network economic perspective focusing on the underlying concepts of congestion, application-agnosticism and layer separation. It can be shown that within the current European regulatory framework the adverse use of TM by network operators is no cause for concern as long as regulatory objectives are fulfilled and significant market power is adequately disciplined. Furthermore, entrepreneurial search processes for optimal price and quality differentiation may require the implementation of TM practices which deviate from strict application-agnosticism and thus violate BEREC's layer separation principle. They may according to BEREC be labeled unreasonable. Instead of the complex case-by-case assessment inducing regulatory micro-management necessary in BEREC's framework, an alternative from a network economic perspective is proposed. Based on an economic understanding of congestion, a market-driven interpretation of applicationagnosticism and a corresponding layer separation constitute the main pillars of a resilient and dynamic understanding of TM.
Keywords: L51; L86; L96; 330